Crystallization kinetics and morphology of melt spun poly(ethylene terephthalate) nanocomposite fibers - R. R. Hegde; G. S. Bhat; B. Deshpande (eXPRESS Polymer Letters)
Natural nanoclay closite Na+ incorporated melt spun poly(ethylene terephthalate) (PET) fibers were investigated for crystallization kinetics and morphology. Nature of clay dispersion and nanocomposite morphology were assessed using wide angle X-ray diffraction (WAXD) and transmission electron microscopy (TEM). Fiber mechanical properties were measured using single fiber tensile test. Combination of scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) was used to investigate the fiber failure mode. Among nanocomposite PET fibers, sample with 1% clay performed better. WAXD and TEM micrographs of the fibers revealed intercalated and delaminated morphology. Size of agglomerate increased with percentage of add-on. SEM surface images showed significant variation in fiber diameter, voids and imperfections. Cross-sections of fractured surfaces revealed the presence of clay agglomerates at failure spots. Nanoclay reinforcement did not incur mechanical property benefits due to increase in voids and agglomerates in fiber section, especially at loading levels higher than one percent.